Microfabricated ultra-thin all-polymer thermal ground planes - Lewis, Ryan; Liew, Li-Anne; Xu, Shanshan; Lee, Yung-Cheng; Yang, Ronggui (Chinese science bulletin, 2015)
Abstract Thermal ground planes, or planar heat pipes, can provide highly effective heat transfer by utilizing phase change of an encapsulated fluid. In this article, a flexible thermal ground plane （FTGP） was fabricated using poly- mer materials. Kapton was employed as a casing material while micropatterned SU-8 was used to provide both a liquid wicking structure and pillars to support the casing over a vapor core. An ultra-thin TiO2 film was deposited over the SU-8 and Kapton via atomic layer deposition, which acted as both a moisture barrier and a hydrophilic coating on polymer surfaces. The assembled FTGP has a thickness of 0.30 mm, an active area of 20 mm~ 60 mm, heater area of 20 mm x 10 ram, and can operate with a heat load up to 9.54 W, with an effective thermal con- ductivity up to 541 W/（m K）.